(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the history, stages of development, and current state of phraseological units in English and Uzbek linguistics. The specific features of phraseologisms in languages belonging to two different families and the views of scholars who have studied them are comparatively studied